Schooling in the Nordic countries during the COVID-19 pandemic - Caroline King Barnard Hall; Inés Hardoy; Martin Lundin (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2022)
This article provides an overview of the extent of school closures and the use of distance learning in the Nordic countries during the COVID-19 pandemic (March 2020 to June 2021). Taking the preparedness of the educational systems into consideration and combining several reports summarising student and teacher experiences with research on the causal impact of distance learning, we discuss expected and revealed effects on student outcomes in the short and long term. Survey evidence indicates that the Nordic education systems were relatively well-prepared for a transition to distance learning in terms of access to digital technology. Overall, Sweden stands out as having kept compulsory schools open to a greater extent than the other countries, while policies put in place at the upper secondary level were more similar across the region. The literature suggests that school closures can be expected to have long term negative effects on skill formation and future earnings and that the negative impacts are likely to be larger for more disadvantaged students and larger the younger the students are when exposed to remote instruction. Given the extent of school closures, students in compulsory schooling in Norway, Finland and Denmark seem particularly vulnerable as do disadvantaged groups of upper secondary school students in all of the countries, since they have been exposed to distance learning for the longest periods. The size of the long-term effects will eventually depend on the success of policies put in place to counteract the potential negative effects.
Keywords: I21; 124; I26; I28; 330; school closures; distance learning; COVID-19; student performance